Unemployment and social stigma: Naming, blaming and shaming of educated youth in rural Khyber Pakhtunkhwa province of Pakistan. Issue 7 (19th March 2020) - Shah, Rahat; Jafeer, Qurat-Ul-Ain; Saeed, Sadia; Aslam, Saba; Ali, Ijaz
Abstract : Purpose: This article aims to highlight the stigmatization attached to the unemployment of educated youth in rural regions of Khyber Pakhtunkhwa province of Pakistan. Design/methodology/approach: The study explicates the subjective experiences of the youth as being unemployed and societal attitudes toward them through an in-depth qualitative approach. A total of 30 unemployed male individuals were interviewed through an interview guide. Findings: The study reveals that unemployed individuals are stigmatized and discriminately treated. They experience the difference in social support from their family and friends during unemployment, which is a discouraging aspect. This finding is in contrast to the existing literature on the subject in which family and friends are described as a major source of social support. As the study is conducted in the rural context, it is observed that local factors coupled with the joint family system have intensified negative attitudes toward the unemployed youth. Subsequently, the negative societal treatment serves as a factor for psychological challenges in their lives. Originality/value: This article serves the need of exploring the experiences of unemployed individuals precisely in the Pakistani context.